Design Strategies Emerging from the Mayan Market Port Tulum: The Case of El Castillo - Paiva, Thaís Daniela Gomes; Arriagada, Carlos Andrés Hernández; Côrrea, Paulo Roberto; Herrera, Grecia Michelle Hernández; Costa, Beatriz Pizzato Angi (Latin American Journal of the Built Environment & Sustainability, 2025)
Objective - To analyze the historical and cultural relevance of the Tulum archaeological site from the perspective of Mayan trade, identifying its importance through the territorial characteristics of the commodification of delicacies that characterized the Mayan ascendancy period—the Classic Period. To understand the importance of product exchange logistics applied at the time through intermediaries along the Riviera Maya coast. Also, to understand the importance of technology and knowledge of land and sea geographic data among the Mayans, factors that aided the naval development of the landscape’s great iconic buildings. Thus, the El Castillo lighthouse emerges as a case study. Methodology - This research will be developed through a qualitative, exploratory, and descriptive approach in the field of archaeology. The qualitative systematization of the work provides a deep understanding of the cultural, historical, and social significance, as well as enabling an understanding of the technical capabilities of the El Castillo Market Port. Originality/Relevance - The study develops an understanding of the social and economic construction of port logistics among the Mayan peoples, highlighting, through its discussion, the relationship between culture, history, and the environment, a topic still rarely discussed in the scientific literature. Furthermore, the article raises questions about the contemporary city of Tulum in relation to the challenges it faces. Results - The research is expected to contribute to a better understanding and identification of Mayan environmental, social, and cultural practices, as well as to the importance of port logistics for the formulation of effective conservation strategies. The resulting diagnosis can inform future architectural and urban planning interventions, and is useful for historical and environmental heritage preservation agencies. Theoretical/Methodological Contributions - The study highlights the need to understand heritage as part of the integrated urban-environmental system. The research demonstrates the relevance of an interdisciplinary approach, combining documentary analysis and territorial observation, to support strategies that reconcile cultural conservation and sustainability. Social and environmental contributions - The study aims to demonstrate that heritage preservation in Tulum is intrinsically linked to ecosystem protection and integration with the city’s culture and population. The conservation of green areas, which serve as a natural protective barrier for historical assets, reduces their vulnerability to climate change.